The effect of the smoking process on polycyclic aromatic hydrocarbons contents in Hashemi and Domsiah rice cultivars. Issue 2 (15th December 2020) - Fazeli, Fatemeh; Seyedain Ardabili, Seyyed Mahdi; Piravivanak, Zahra; Honarvar, Masoud; Mooraki, Nargess
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a group of lipophilic organic compounds consisting of two or more fused aromatic rings. Ingestion through contaminated food and water is a major route of human exposure to PAHs. Smoked products are important sources of dietary PAHs. Therefore, this study evaluated the effect of smoking times on the content of PAH compounds. The result showed that smoking duration had a significant effect on Benzo[a]pyrene (BaP) and 4PAH indices in both cultivars (Hashemi and Domsiah) between the three test groups (nonsmoked rice, rice smoked for 10 and 14 days) ( p  < .05). The level of BaP index in nonsmoked rice samples was lower than the permitted limit (1 μg/kg), but increased after smoking and exceeded the permitted limit. The 4PAH index was too high in both nonsmoked and smoked rice samples and the smoking process increased further. Finally, the smoking process had a significant direct effect on PAH compounds in Hashemi and Domsiah rice during the 14 days after smoking. Practical applications: The polycyclic aromatic compounds have been identified as toxic compounds in most smoked food products such as meat, rice, and fish. The staple food of most people in the Middle East is rice, whose smoked form is mostly consumed. This source contains high amounts of polycyclic aromatic hydrocarbons. It is almost impossible to accurately measure them by traditional methods. The combination of the ultrasound‐assisted extraction method and high‐performance liquid chromatography with a fluorescence detection (HPLC/FLD) device can be a great help in accurately identifying these compounds in two varieties of smoked rice. Since most smoked rice workshops were traditionally built and operated, combustion conditions were usually not controlled properly and control criteria were not considered; therefore, smoked rice with high amounts of PAH compounds was produced. There is a need for replacement of the traditional smoking process with the industrial smoking process, use wood instead of paddy, revise the rice standard, and establish control limits for PAH compounds, especially for smoked rice.